Both SUMOylation and ubiquitination of TFE3 fusion protein regulated by androgen receptor are the potential target in the therapy of Xp11.2 translocation renal cell carcinoma. Issue 4 (22nd April 2022) - Liu, Ning; Chen, Yi; Yang, Lei; Shi, Qiancheng; Lu, Yanwen; Ma, Wenliang; Han, Xiaodong; Guo, Hongqian; Li,, Dongmei; Gan,, Weidong
ABSTRACT: Background: The aggressiveness of renal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusion (Xp11.2 translocation RCC [Xp11.2 tRCC]) is age‐dependent, which is similar to the overall trend of reproductive endocrine hormones. Therefore, this study focused on the effect and potential mechanism of androgen and androgen receptor (AR) on the progression of Xp11.2 tRCC. Methods: The effects of androgen and AR on the proliferation and migration of Xp11.2 tRCC cells were first evaluated utilising Xp11.2 tRCC cell lines and tissues. Because Transcription factor enhancer 3 (TFE3) fusion proteins play a key role in Xp11.2 tRCC, we focused on the regulatory role of AR and TFE3 expression and transcriptional activity. Results: When Xp11.2 tRCC cells were treated with dihydrotestosterone, increased cell proliferation, invasion and migration were observed. Compared with clear cell RCC, the positive rate of AR in Xp11.2 tRCC tissues was higher, and its expression was negatively associated with the progression‐free survival of Xp11.2 tRCC. Further studies revealed that AR could positively regulate the transcriptional activity of TFE3 fusion proteins by small ubiquitin‐related modifier (SUMO)‐specific protease 1, inducing the deSUMOylation of TFE3 fusion. On the other hand, UCHL1 negatively regulated by AR plays a role in the deubiquitination degradation of the PRCC‐TFE3 fusion protein. Therefore, the combination of the AR inhibitor MDV3100 and the UCHL1 inhibitor 6RK73 was effective in delaying the progression of Xp11.2 tRCC, especially PRCC‐TFE3 tRCC. Conclusions: Androgen and AR function as facilitators in Xp11.2 tRCC progression and may be a novel therapeutic target for Xp11.2 tRCC. The combined use of AR antagonist MDV3100 and UCHL1 inhibitor 6RK73 increased both the SUMOylation and ubiquitination of the PRCC‐TFE3 fusion protein Abstract : Androgen receptor (AR) regulates the SUMO modification of the TFE3 fusion proteins by small ubiquitin‐related modifier‐specific protease 1. AR affects the ubiquitination of the PRCC‐TFE3 fusion protein by regulating UCHL1 negatively. Targeting AR and UCHL1 may serve as a novel target for Xp11.2 translocation renal cell carcinoma therapy.